Racism and mental health among university students in Mexico City Racismo y salud mental en estudiantes universitarios de la Ciudad de México - Luis Ortiz-Hernández; Sandra Compeán-Dardón; Elizabeth Verde-Flota; Maricela Nanet Flores-Martínez (Instituto Nacional de Salud Pública, 2011)
OBJECTIVE: To assess whether differences exist in experiences of discrimination, perceptions of physical attractiveness, socioeconomic position, and mental health according to student's skin color. MATERIALS AND METHODS: The population included students from a public university in Mexico City. The following three groups were created based on skin color: white, light brown, and brown. By means of regression models, we evaluated whether differences in mental health according to skin color could be due to experiences of discrimination, perceptions of physical attractiveness, and/or socioeconomic position. RESULTS: Students with brown skin had lower levels of self-esteem and vitality and higher levels of fatigue and alcohol consumption. These differences were explained by more frequent experiences of discrimination and because students with brown skin perceived themselves as less attractive. CONCLUSIONS: This is one of the first studies to document the possible effects of racism on mental health among the urban population. Verification of these findings in representative samples is required. OBJETIVOS: Conocer si existen diferencias en experiencias de discriminación, percepción del atractivo físico, posición socioeconómica y salud mental en función del color de la piel. MATERIAL Y MÉTODOS: La población consistió en estudiantes de una universidad de la Ciudad de México. A partir del color de piel se formaron tres grupos: blancos, morenos claros y morenos. Mediante modelos de regresión se evaluó si las diferencias en salud mental de acuerdo al color de piel se debían a experiencias de discriminación, percepción del atractivo físico y/o posición socioeconómica. RESULTADOS: Los que tenían piel morena tuvieron niveles más bajos de autoestima y vitalidad, pero más altos de cansancio y de consumo de alcohol. Estas diferencias fueron explicadas por las experiencias de discriminación y porque los estudiantes morenos se percibían menos atractivos. CONCLUSIONES: Por primera vez se documentan los posibles efectos del racismo en la salud mental en población urbana de México.